PTH1R Actions on Bone Using the cAMP/Protein Kinase A Pathway - Martin, T. John (Frontiers in Endocrinology, 2022)
After the initial signaling action of parathyroid hormone (PTH) on bone was shown to be activation of adenylyl cyclase , its target was found to be cells of the osteoblast lineage, to the exclusion of osteoclasts and their precursors. This led to the view that the osteoblast lineage regulated osteoclast formation, a proposal that was established when the molecular mechanisms of osteoclast formation were discovered. This is in addition to the effect of PTH1Rv signaling throughout the osteoblast differentiation process to favour the formation of bone-forming osteoblasts. Initial signaling in the PTH target cells through cAMP and protein kinase A (PKA) activation is extremely rapid, and marked by an amplification process in which the later event, PKA activation, precedes cAMP accumulation in time and is achieved at lower concentrations. All of this is consistent with the existence of “spare receptors”, as is the case with several other peptide hormones. PTH-related protein (PTHrP), that was discovered as a cancer product, shares structural similarity with PTH in the amino-terminal domain that allows the hormone, PTH, and the autocrine/paracrine agent, PTHrP, to share actions upon a common G protein coupled receptor, PTH1R, through which they activate adenylyl cyclase with equivalent potencies. Studies of ligand-receptor kinetics have revealed that the PTH/PTH1R ligand-receptor complex, after initial binding and adenylyl cyclase activation at the plasma membrane, is translocated to the endosome, where adenylyl cyclase activation persists for a further short period. This behaviour of the PTH1R resembles that of a number of hormones and other agonists that undergo such endosomal translocation. It remains to be determined whether and to what extent the cellular effects through the PTH1R might be influenced when endosomal is added to plasma membrane activation.